﻿New records of two cusk eels of the genus Neobythites from Taiwan, with a northward range extension of N. australiensis Nielsen, 2002 (Actinopterygii: Ophidiiformes: Ophidiidae) - Yo Su; Hsiu-Chin Lin; Hsuan-Ching Ho (Acta Ichthyologica et Piscatoria, 2023)
Two species of cusk eels, Neobythites australiensis Nielsen, 2002 and Neobythites japonicus Uiblein et Nielsen, 2023 were collected from southwestern and northeastern Taiwan, respectively. They represent the first record of both species from Taiwan. The former specimen represents the first record from the Northern Hemisphere, and the latter specimen represents the second record of N. japonicus. As a result, eight species of Neobythites are recognized in Taiwan. We provide a detailed description of the two specimens, comparison with other available specimens, discussion of intraspecific variations, and a dichotomous key to species of Neobythites in Taiwan.